The Supremacy of Law and Application of International Sanctions (Summary) - М. V. Keshner (Московский журнал международного права)
Compliance with the legitimacy is fundamental to ensure sustainable international legal order, which to a large extent dependent on the total understanding of when use of coercive measures is legitimate. The article examines the rule of law in the application of international sanctions. Analyzes the problem of the legitimacy of international sanctions, determines its relationship with compliance issues sanction authority. The sanctions competence of other international organizations shall strictly comply with the Charter of the United Nations, and in their implementation, they are not allowed to exceed the sanctions stemming from the charter authority. This provision is essential to the legitimacy of the use of sanctions by other international organizations. The article substantiates the basic criteria of legitimacy of international sanctions, which is necessary to take into account when making the UN Security Council decision to impose international sanctions.